Unlocking Scientific Potential: Using Smartphones as Mobile Mini-Labs to Improve Students’ Science Process Skills - Nurlaini, Nurlaini; Asyhar, Rayandra; Tanti, Tanti (JIPF (Jurnal Ilmu Pendidikan Fisika), 2025)
This study aims to analyze the effectiveness of physics-based learning based on smartphone-integrated Group Investigation (GI) as a mobile mini-labs to improve students' science process skills in learning physics. This study is a quasi-experimental research with a post-test control group design. The research sample consisted of 72 students in class XI of Science at SMAN 10 Jambi City which was divided into an experimental class (n=36) and a control class (n=36). Data were collected using science process skills observation sheets and a learning implementation checklist. The results of the analysis using the Mann-Whitney U test showed a significant difference in science process skills between the two groups (p<0.05), with a high effect size value (r=0.86). Experimental classes showed higher improvements in all dimensions of science process skills, especially in communication, data collection and processing, and experiment design. Observation of learning implementation showed effective implementation with an average implementation score of 3.75 out of a maximum score of 4. These findings indicate that smartphone-integrated GI-based physics learning as mobile mini-labs is effective in improving students' science process skills, and provides important implications for the development of innovative physics-based learning strategies based on technology.